1995
DOI: 10.1111/j.1365-2621.1995.tb05622.x
|View full text |Cite
|
Sign up to set email alerts
|

Frozen Carrots Texture and Pectic Compotients as Affected by Low‐Temperature‐Blanching and Quick Freezing

Abstract: MATERIALS & METHODESCarrots preheated for 2 hr at 60°C and then cooked became firmer than raw or cooked carrots. After preheating, the amount of high methoxyl pectin decreased, and low methoxyl pectin increased. Firmness of carrots decreased through freezing then thawing, but preheated carrots retained firmer texture than those blanched in boiling water. Quick-freezing resulted in better texture than slow-freezing. Loss in texture was accompanied by release of pectin. Slow-freezing accelerated release of pecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(48 citation statements)
references
References 11 publications
4
43
1
Order By: Relevance
“…Calcium chloride was also contributed to increased firmness due to the interaction of calcium with pectins and other cellular wall components of the plant cellular matrix (Gras et al, 2003). Fuchigami, Miyazaki and Hyakumoto (1995) observed that the worsened texture of frozen tomatoes was accompanied by a decrease in the content of pectic compounds. Lisiewska and Kmiecik (2000) also reported that the level of protopectins and pectins were significantly reduced by the freezing process itself and during subsequent frozen storage of tomato tissue.…”
Section: Osmodehydrofreezing and Freezingmentioning
confidence: 99%
“…Calcium chloride was also contributed to increased firmness due to the interaction of calcium with pectins and other cellular wall components of the plant cellular matrix (Gras et al, 2003). Fuchigami, Miyazaki and Hyakumoto (1995) observed that the worsened texture of frozen tomatoes was accompanied by a decrease in the content of pectic compounds. Lisiewska and Kmiecik (2000) also reported that the level of protopectins and pectins were significantly reduced by the freezing process itself and during subsequent frozen storage of tomato tissue.…”
Section: Osmodehydrofreezing and Freezingmentioning
confidence: 99%
“…Contract/grant sponsor : Biotechnology and Biological Sciences Research Council. heating process. This work was also complemented by Fuchigami et al (1994Fuchigami et al ( , 1995 who studied the e †ect of freezing and thawing by characterising the Ðrmness with a creepmeter. Other methodology was adopted by Ramana and Taylor (1992a,b) who evaluated the rheological properties respectively on carrot discs and carrot cell and cell wall suspensions by oscillatory measurements during freezing and cooking.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, preheating of various vegetables such as potato (Bartolome and Johan, 1972;Abu-Ghannam and Crowley, 2006), sweet potato (Truong et al, 1998;Fuchigami et al, 2002), and carrot (Fuchigami et al, 1995;Ng and Waldron, 1997;Smout et al, 2005) has been investigated. However, most examinations of vegetable preheating have been carried out for 30 min to 2 h in hot water, which might cause the elution of water-soluble components.…”
Section: Introductionmentioning
confidence: 99%